Mid-western State programme, 1975-80 of the third national development plan, 1975-80 - Mid-western State (Nigeria). (Benin City : Ministry of Economic Development, 1975)
The primary objective of the programme is to consolidate the achievements of past development efforts especially in agriculture, manufacturing, transport, education and health.
oif 12/04/2019
Nigeriana
Keywords: Economic policy; Social policy; Regional planning; Nigeria, Mid-western State